IDEOLOGICAL REPRESENTATION THROUGH LEXICAL CHOICES IN POLITICAL WAR NEWS HEADLINES - Kamolova Kamola Xurshid qizi (International Journal of Literature and Language Studies, 2026)
This article investigates how lexical choices in political war news headlines function as instruments of ideological representation. Working within the framework of Critical Discourse Analysis (CDA) and drawing on appraisal theory, the study analyses a purposively assembled corpus of war-related headlines from ideologically divergent news outlets. The analysis isolates five recurrent lexical mechanisms—referential naming, over-lexicalization, evaluative modification, euphemism and dysphemism, and metaphorical framing and demonstrates how each contributes to the discursive construction of in-groups and out-groups. The findings indicate that headline writers systematically exploit lexical asymmetry to legitimize certain actors while delegitimizing others, often through choices that pass unnoticed by the ordinary reader. The study contributes to media-linguistic scholarship by offering a replicable analytical model linking micro-level word selection to macro-level ideological positioning.